(untitled) - Schramm, David N. (Singapore, 1996)
The prime focus of the book is on Big Bang cosmology and the role of primordial nucleosynthesis in establishing the modern consensus on the Big Bang. This leads into the connection of cosmology to particle physics and the constraints put on various elementary particles by astrophysical arguments. Big Bang Nucleosynthesis has also led to the argument for nonbaryonic dark matter and is thus related to the major problem in physical cosmology today, namely, structure formation. The nuclear-particle interface with astrophysics also extends to the other topics of major interest such as the age of the universe, cosmic rays, supernovae, and solar neutrinos, each of which will be discussed in some detail. Each section contains historical papers, current papers, and frequently a popular article on the subject which provides an overview of the topic
Keywords: Nuclear astrophysics,Astrophysics,Big bang theory,Vật lý học thiên thể hạt nhân,Vật lý học thiên thể,Lý thuyết Big bang